IMPLEMENTASI SISTEM INFORMASI IMPLEMENTASI SISTEM INFORMASI PEMASARAN BERBASIS DIGITAL PADA HOME INDUSTRY JAJANAN TRADISIONAL - ABRYANDOKO, EKO WAHYU; Istiqomah, Ilmi Nurul (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2020)
This study aims to determine the description of marketing information systems that are applied to the traditional home snacks of Pak Dicky and analyze the problems of the current system to be developed in the form of marketing information system design to promote traditional snacks that are being forgotten. This research was carried out in the marketing section of Pak dicky's traditional home industry snacks located in the district of cotton - Bojonegoro. This type of research is a qualitative research with action research approach. Data sources used are primary data and secondary data obtained using data collection methods in the form of observation, interviews, and documentation. The results showed that the marketing information system in the traditional home snacks of Pak Dicky still uses a conventional model that still has various weaknesses and lacks efficiency. These weaknesses include the promotion of social media that is less effective and efficient in providing information to prospect customers. Recommendations from existing customers are not supported by complete information sources that can be given when needed. limited marketing reach. Digital models and existing networks have not yet been utilized. The design of the implementation of marketing information systems for digital-based promotions can be implemented by Pak Dicky's traditional hawker industry as an effort to overcome the ongoing marketing problems in providing information about traditional hawker products offered.